2021
DOI: 10.3390/microorganisms9112256
|View full text |Cite
|
Sign up to set email alerts
|

Development of Various Leishmania (Sauroleishmania) tarentolae Strains in Three Phlebotomus Species

Abstract: Leishmania (Sauroleishmania) tarentolae is transmitted by reptile-biting sand flies of the genus Sergentomyia, but the role of Phlebotomus sand flies in circulation of this parasite is unknown. Here, we compared the development of L. (S.) tarentolae strains in three Phlebotomus species: P. papatasi, P. sergenti, and P. perniciosus. Laboratory-bred sand flies were membrane-fed on blood with parasite suspension and dissected on days 1 and 7 post blood meal. Parasites were measured on Giemsa-stained gut smears an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
31
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
2

Relationship

3
4

Authors

Journals

citations
Cited by 15 publications
(34 citation statements)
references
References 50 publications
3
31
0
Order By: Relevance
“…Although it is generally accepted that Sauroleishmania parasites are transmitted by reptile-biting sand flies of the genus Sergentomyia , the role of other sand flies in Sauroleishmania transmission should be reconsidered. The susceptibility of Phlebotomus species to Sauroleishmania infections has been experimentally demonstrated by several authors [ 13 , 14 ] and now confirmed in the present study. Some Phlebotomus species were reported to feed on reptiles [ 4 , 13 , 27 ], and recent molecular detection of Leishmania ( Sauroleishmania ) tarentolae in Phlebotomus spp.…”
Section: Discussionsupporting
confidence: 88%
See 3 more Smart Citations
“…Although it is generally accepted that Sauroleishmania parasites are transmitted by reptile-biting sand flies of the genus Sergentomyia , the role of other sand flies in Sauroleishmania transmission should be reconsidered. The susceptibility of Phlebotomus species to Sauroleishmania infections has been experimentally demonstrated by several authors [ 13 , 14 ] and now confirmed in the present study. Some Phlebotomus species were reported to feed on reptiles [ 4 , 13 , 27 ], and recent molecular detection of Leishmania ( Sauroleishmania ) tarentolae in Phlebotomus spp.…”
Section: Discussionsupporting
confidence: 88%
“…Morphological stages of the parasites were determined as described previously for members of the subgenus Sauroleishmania [ 14 ]: (i) long nectomonad promastigotes (body length ≥ 14 μm); (ii) short nectomonad promastigotes (body length < 14 μm and flagella length < 2-fold the body length); (iii) metacyclic-like promastigotes (body length < 14 μm and flagella length ≥ 2-fold body length); (iv) amastigote-like forms; and (v) haptomonad promastigotes. Differences in number of metacyclic-like stages were tested by the Chi-square ( χ 2 ) tests using SPSS software version 27 (SPSS IBM Corp.).…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…In the dixenous Leishmania genus, three types of development have been recognized: suprapylarian development, typical of the subgenus Leishmania , is restricted to the mesenteron; peripylarian development, known in the subgenus Viannia and some Sauroleishmania species, also involves multiplication in the hindgut prior to the anterior migration and colonization of the stomodeal valve; and finally, hypopylarian development in other Sauroleishmania species is restricted to the hind gut ( Lainson and Shaw, 1987 ). Occurrence of low numbers of Leishmania promastigotes in MT, reported in natural or experimental infections, has been interpreted as a consequence of peristaltic backwash from the midgut ( Lainson and Shaw, 1968 ) and invasion of MT by Leishmania has been more frequently observed in unnatural vector- parasite pairs or atypical experimental conditions like maltose or fructose diet and reduced temperature ( Rangel et al., 1985 ; Walters et al., 1987 ; Anez et al., 1989 ; Nieves and Pimenta, 2000 ; Ticha et al., 2021 ). In the dixenous genus Endotrypanum , which is closely relative to Porcisia , development in MT has been observed more frequently than in Leishmania , but in variable proportion in different sand fly species and in a lower percentage of females compared with midgut infections ( Shaw, 1981 ; Franco et al., 1997 ).…”
Section: Discussionmentioning
confidence: 99%